SPL integrated with Microservices: a hybrid architectural proposal for multitenant SaaS - Oliveira, Manoel Marisergio Alves de; Lima, Rian Carlos Silva; Costa, Marcos Vinicius Lima da; Trindade, Cláudio Silva; Queiroz, Paulo Gabriel Gadelha (Anais do Simpósio Brasileiro de Componentes, Arquiteturas e Reutilização de Software (SBCARS), 2023)
Designing systems to serve a large number of people, who have similar demands, but also have varied needs and generate a huge volume of data, requires a software architecture that allows constant evolution, is easy to maintain, and has the ability to scale smartly. The SPL technique with microservices architecture seems promising to meet these requirements, but this integration is not trivial. Thus, we conduct a SLR that identified 3 architectures that proposed the combination of these techniques. However, the architectures found were complex and reduced time-to-market, as they proposed the implementation of all resources through microservices. Thus, in order to reduce the complexity of development and, consequently, reduce the time to market, this work presents a proposal for the design of a hybrid SPL architecture, through the combination of large backend APIs and microservices. In addition, this research paper presents a case study that consisted of defining the architecture of a medical clinics SPL as a Multi-tenant Software as a Service. Finally, we compare the complexity of the architecture generated using our approach, with a microservice architecture constructed using other approach found in literature.